Resolution of the 8th Congress with International Participation "Сontrol and prevention of healthcare associated infections (ISMP-2020)" (Moscow, November 25–27, 2020) - V. G. Akimkin (Журнал микробиологии, эпидемиологии и иммунобиологии, 2021)
.